Cellular prion protein distribution in the vomeronasal organ, parotid, and scent glands of white-tailed deer and mule deer. Issue 1 (31st December 2022) - Ness, Anthony; Jacob, Aradhana; Saboraki, Kelsey; Otero, Alicia; Gushue, Danielle; Martinez Moreno, Diana; de Peña, Melanie; Tang, Xinli; Aiken, Judd; Lingle, Susan; McKenzie, Debbie
ABSTRACT: Chronic wasting disease (CWD) is a contagious and fatal transmissible spongiform encephalopathy affecting species of the cervidae family. CWD has an expanding geographic range and complex, poorly understood transmission mechanics. CWD is disproportionately prevalent in wild male mule deer and male white-tailed deer. Sex and species influences on CWD prevalence have been hypothesized to be related to animal behaviours that involve deer facial and body exocrine glands. Understanding CWD transmission potential requires a foundational knowledge of the cellular prion protein (PrP C ) in glands associated with cervid behaviours. In this study, we characterized the presence and distribution of PrP C in six integumentary and two non-integumentary tissues of hunter-harvested mule deer ( Odocoileus hemionus ) and white-tailed deer ( O. virginianus ). We report that white-tailed deer expressed significantly more PrP C than their mule deer in the parotid, metatarsal, and interdigital glands. Females expressed more PrP C than males in the forehead and preorbital glands. The distribution of PrP C within the integumentary exocrine glands of the face and legs were localized to glandular cells, hair follicles, epidermis, and immune cell infiltrates. All tissues examined expressed sufficient quantities of PrP C to serve as possible sites of prion initial infection, propagation, and shedding.